Spatiotemporally resolved electrodynamic properties of a Sun‐aligned arc over Resolute Bay. Issue 11 (17th November 2015) - Perry, G. W.; Dahlgren, H.; Nicolls, M. J.; Zettergren, M.; St.‐Maurice, J.‐P.; Semeter, J. L.; Sundberg, T.; Hosokawa, K.; Shiokawa, K.; Chen, S.
Abstract: Common volume measurements by the Resolute Bay Incoherent Scatter Radar‐North (RISR‐N) and Optical Mesosphere and Thermosphere Imagers (OMTI) have been used to clarify the electrodynamic structure of a Sun‐aligned arc in the polar cap. The plasma parameters of the dusk‐to‐dawn drifting arc and surrounding ionosphere are extracted using the volumetric imaging capabilities of RISR‐N. Multipoint line‐of‐sight RISR‐N measurements of the plasma drift are inverted to construct a time sequence of the electric field and field‐aligned current system of the arc. Evidence of dramatic electrodynamic and plasma structuring of the polar cap ionosphere due to the arc is described. One notable feature of the arc is a meridionally extended plasma density depletion on its leading edge, located partially within a downward field‐aligned current region. The depletion is determined to be a by‐product of enhanced chemical recombination operating on a time scale of 15 min. A similarly shaped electric field structure of over 100 mV/m and line‐of‐sight ion temperatures nearing 3000 K were collocated with the depletion. Key Points: The electrodynamic structure of a Sun‐aligned arc is resolved in time and space Plasma density depletion formed by intense E fields and FACs of Sun‐aligned arc Large E fields and ion temperatures are collocated with the density depletion